The Implementation of Problem Based Learning Model to Improve Students’ Reading Comprehension Achievement in Learning Narrative Text - Sari, Meilitha (Lembaga Bale Literasi, 2023)
This study was carried out because of the author's discovery that the majority of her pupils struggle with reading comprehension and lack interest in studying narrative texts. By implementing the Problem-based Learning Model with the tenth-grade students of Accountant 1 Class of SMK N 1 Keluang, this study seeks to increase students' reading comprehension achievement in learning Narrative Text. In doing this research, action research was used. The data were collected through knowledge assessment, attitude assessment, and observation of students’ presentation skill. The findings of the study showed that there was a significant difference between the students’ reading comprehension achievement. The students’ average score improves through using Problem Based Learning model. It means that the implementation of PBL model was effective to improve reading comprehension achievement of the tenth-grade students of accountant 1 Class of SMKN 1 Keluang, Musi Banyuasin.